Promoting scholarship in improvement science: A model for academic clinical departments - Stephen G. DeVoe; Amanda G. Kennedy; Bradley J. Tompkins; Juvena R. Hitt; Eric L. Gagnon; Polly E. Parsons; Allen B. Repp (Wiley, 2023)
Abstract Introduction Clinical departments at academic medical centers strive to deliver clinical care, provide education and training, support faculty development, and promote scholarship. These departments have experienced increasing demands to improve the quality, safety, and value of care delivery. However, many academic departments lack a sufficient number of clinical faculty members with expertise in improvement science to lead initiatives, teach, and generate scholarship. In this article, we describe the structure, activities, and early outcomes of a program within an academic department of medicine to promote scholarly improvement work. Methods The Department of Medicine at the University of Vermont Medical Center launched a Quality Program with three primary goals: (a) improve care delivery, (b) provide education and training, and (c) promote scholarship in improvement science. The program serves as a resource center for students, trainees and faculty, offering education and training, analytic support, consultation in design and methodology, and project management. It strives to integrate education, research, and care delivery to learn, apply evidence and improve health care. Results Over the first 3 years of full implementation, the Quality Program supported an average of 123 projects annually, including prospective clinical quality improvement initiatives, retrospective assessment of clinical programs and practices, and curriculum development and evaluation. The projects have yielded a total of 127 scholarly products, defined as peer‐reviewed publications and abstracts, posters, and oral presentations at local, regional, and national conferences. Conclusions The Quality Program may serve as a practical model for promoting care delivery improvement, training, and scholarship in improvement science while advancing the goals of a learning health system at the level of an academic clinical department. Dedicated resources within such departments offer the potential to enhance care delivery while promoting academic success for faculty and trainees in improvement science.